EHealth intervention to manage symptoms for patients with cancer on immunotherapy (SOFIA): a study protocol for a randomised controlled external pilot trial - Sauer, Christina; Krauß, Jürgen; Jäger, Dirk; Zschäbitz, Stefanie; Haag, Georg Martin; Walle, Thomas; Sauer, Simeon; Kiermeier, Senta; Friederich, Hans-Christoph; Maatouk, Imad (BMJ open, 2021)
Introduction Immune checkpoint therapy (ICT) is associated with a distinct pattern of immune-related adverse events (irAEs) caused by inadvertently redirecting immune responses to healthy tissues. IrAEs can occur at any time; however, in most cases, they arise during the first 14 weeks of the beginning of immune checkpoint blockade. In many cases, immunotherapy must be discontinued due to irAEs. Early detection of irAEs triggers the temporary withholding of ICT or initiation of short-term immunosuppressive treatment, is crucial in preventing further aggravation of irAEs and enables safe re-exposure to ICT. This prospective study aims to evaluate the feasibility of an eHealth intervention for patients under immunotherapy (managing symptoms of immunotherapy, SOFIA). The SOFIA-App consists of two components: SOFIA-Monitoring, a tool to rate patient-reported outcomes (PROs) including irAEs, and SOFIA-Coaching, which provides important information about cancer-specific and immunotherapy-specific topics and the counselling services of the National Centre for Tumour Diseases (NCT) Heidelberg. - Methods and analysis We outlined a patient-level two-arm randomised controlled pilot trial of the intervention (SOFIA) versus no-SOFIA for patients with cancer beginning an immunotherapy, aged ≥18 years, recruited from the NCT, Heidelberg. Feasibility outcomes include: recruitment rate; drop-out rate; reasons for refusal and drop-out; willingness to be randomised, utilisation rate of SOFIA-Monitoring and utilisation time of SOFIA-Coaching, physicians utilisation rate of the PROs; feasibility of the proposed outcome measures and optimal sample size estimation. The clinical outcomes are measures of quality of life, psychosocial symptoms, self-efficacy, physician-patient communication and medical process data, which are assessed at the beginning of the intervention, postintervention and at 6-month follow-up. - Ethics and dissemination This trial protocol was approved by the Ethical Committee of Heidelberg University, Germany (Reference, S-581/2018). - Trial registration number We registered the study in the German Clinical Trial Register (Reference: DRKS00021064). Findings will be disseminated broadly via peer-reviewed empirical journals, articles and conference presentations.